Apolipoprotein E Deficiency Exacerbates Spinal Cord Injury in Mice: Inflammatory Response and Oxidative Stress Mediated by NF-κB Signaling Pathway - Yang, Xuan; Chen, Shurui; Shao, Zhenya; Li, Yuanlong; Wu, He; Li, Xian; Mao, Liang; Zhou, Zipeng; Bai, Liangjie; Mei, Xifan; Liu, Chang (Frontiers in Cellular Neuroscience, 2018)
Spinal cord injury (SCI) is a severe neurological trauma that involves complex pathological processes. Inflammatory response and oxidative stress are prevalent during the second injury and can influence the functional recovery of SCI. Specially, Apolipoprotein E (APOE) induces neuronal repair and nerve regeneration, and the deficiency of Apoe impairs spinal cord-blood-barrier and reduces functional recovery after SCI. However, the mechanism by which Apoe mediates signaling pathways of inflammatory response and oxidative stress in SCI remains largely elusive. This study was designed to investigate the signaling pathways that regulate Apoe deficiency-dependent inflammatory response and oxidative stress in the acute stage of SCI. In the present study, Apoe−/− mice retarded functional recovery and had a larger lesion size when compared to wild-type mice after SCI. Moreover, deficiency of Apoe induced an exaggerated inflammatory response by increasing expression of interleukin-6 (IL-6) and interleukin-1β (IL-1β), and increased oxidative stress by reducing expression of Nrf2 and HO-1. Furthermore, lack of Apoe promoted neuronal apoptosis and decreased neuronal numbers in the anterior horn of the spinal cord after SCI. Mechanistically, we found that the absence of Apoe increased inflammation and oxidative stress through activation of NF-κB after SCI. In contrast, an inhibitor of nuclear factor-κB (NF-κB; Pyrrolidine dithiocarbamate) alleviates these changes. Collectively, these results indicate that a critical role for activation of NF-κB in regulating Apoe-deficiency dependent inflammation and oxidative stress is detrimental to recovery after SCI.